Electronic records: its implications on National Archives Act of Malaysia 44/1966 / Ezza Rafedziawati Kamal Rafedzi - Kamal Rafedzi, Ezza Rafedziawati (2000)
Vision 2020, a national agenda that sets out specific goals and objectives for longterm development for Malaysia. This vision have clearly articulates Malaysian objective towards developed-nation status while moving towards the creation of an information rich society in the information age. To be an information rich society, a variable of related technologies such as computer, software, telecommunications and multimedia are being used to receive, create, process, store and disseminate information. Those activities will create electronic records management. By studying in National Archives Act in other countries; I've seen that many of them had revised their act. Some of them are still reviewing their act in moving towards an information technology era. They are looking for a new definitions, policy, responsibility, storage, preservation and procedures in managing electronic records. National Archives of Malaysia should revised their act. National Archives of Malaysia should be more specific as reference to government and semi government agencies and private agencies